Surface Complexation of Oxytetracycline by Magnetite: Effect of Solution Properties. Issue 2 (31st January 2014) - Rakshit, Sudipta; Sarkar, Dibyendu; Elzinga, Evert J.; Punamiya, Pravin; Datta, Rupali
Abstract : Few studies have reported on the sorptive interactions of oxytetracycline (OTC), a veterinary antibiotic frequently detected in wastewater, surface water, and soils, with common Fe oxide minerals. The primary objective of this study was to investigate the sorption behavior of OTC on magnetite (Fe3 O4 ) as a function of different solution properties such as pH, ionic strength, and initial OTC concentration. Results indicated that sorption of OTC by magnetite was rapid and complete within 24 h. The effect of ionic strength on sorption was negligible at low OTC surface coverage. The sorption envelope indicated that with increasing pH, OTC sorption on Fe3 O4 decreased. Surface complexation modeling of magnetite–OTC interactions suggested the interactions of divalent anionic species of OTC with the magnetite surface. Four possible surface complexation reactions were postulated to explain the pH dependence of OTC sorption, indicating a rather complex potential sorption mechanism. Our results suggest that magnetite has the capability of immobilizing OTC in the environment, which may be of use to scientists in predicting the fate of OTC in Fe‐oxide‐rich soil.